The implementation of post-processing algorithm for ultrasonic testing of welds; IOP Conference Series: Materials Science and Engineering; Vol. 510 : High Technology: Research and Applications (HTRA-2018) - Petrov I. S. Iljya Sergeevich; Vdovenko A.; Dolmatov D. O. Dmitry Olegovich; Sednev D. A. Dmitry Andreevich (2019, 2019)
Title screen